Deceptively simple … The “deception-general” ability and the need to put the liar under the spotlight - Wright, Gordon R.; Berry, Christopher J.; Bird, Geoffrey (Frontiers in Neuroscience, 2013)
This Focused Review expands upon our original paper (You can’t kid a kidder": Interaction between production and detection of deception in an interactive deception task. Frontiers in Human Neuroscience, 6:87). In that paper we introduced a new socially interactive, laboratory-based task, the Deceptive Interaction Task (DeceIT), and used it to measure individuals’ ability to lie, their ability to detect the lies of others, and potential individual difference measures contributing to these abilities. We showed that the two skills were correlated; better liars made better lie detectors (a “deception general” ability) and this ability seemed to be independent of cognitive (IQ) and emotional (EQ) intelligence. Here, following the Focused Review format, we outline the method and results of the original paper and comment more on the value of lab-based experimental studies of deception, which have attracted criticism in recent years. While acknowledging that experimental paradigms may fail to recreate the full complexity and potential seriousness of real-world deceptive behavior, we suggest that lab-based deception paradigms can offer valuable insight into ecologically-valid deceptive behavior. The use of the DeceIT procedure enabled deception to be studied in an interactive setting, with motivated participants, and importantly allowed the study of both the liar and the lie detector within the same deceptive interaction. It is our thesis that by addressing deception more holistically - by bringing the liar into the ‘spotlight’ which is typically trained exclusively on the lie detector – we may further enhance our understanding of deception.